Patient Perspectives of High‐Quality Care on the Liver Transplant Waiting List: A Qualitative Study. Issue 2 (25th September 2019) - Shen, Nicole T.; Wu, Ashley; Farrell, Karen; Ivatorov, Amanda; Dawod, Enad; Raver, Michael; Russo, Nicholas; Robbins, Laura; Safford, Monika; Brown, Robert S.
Abstract : The prevalence of advanced liver disease and listing for liver transplantation is increasing. Prior assessments of quality of care neither incorporate nor emphasize the patient perspective on quality of care, which may impact clinical outcomes. Our aim was to identify patients' perceptions on what constitutes high quality of care, comparing the findings to existing frameworks and assessments to determine if a patient‐derived tool assessing quality of care could facilitate efforts to improve health care. We conducted semistructured interviews of patients wait‐listed for liver transplantation, asking patients to describe the quality of their health care with a specific focus on how coordination, communication, office visits, hospitalizations, and cost affect their perceptions of the quality of their care. Data collection conducted concurrently with analyses determined emerging themes and saturation. Themes were mapped to an existing quality‐of‐care conceptual framework. Qualitative analysis revealed thematic saturation after 15 interviews, and an additional 15 interviews were analyzed that confirmed thematic saturation, maximizing the strength of the results. The 30 patients had a median age of 56 years (range, 32‐72 years) and included 15 (50%) men. Although patients believed they received a high quality of care, which was substantiated on current existing measures, a qualitative analysis suggested that patient priorities emphasized 5 themes not currently assessed: managing expectations, providing education, responding to patient needs, executing the care plan efficiently, and utilizing interdisciplinary communication and coordination of care. In conclusion, transplant candidates perceived 5 themes that constitute quality of care, and existing quality‐of‐care measures do not assess these domains, suggesting a role for creating a patient‐derived quality‐of‐care tool to improve health care and clinical outcomes.